Leveraging Reinforcement Learning for Autonomous Cloud Management and Self-Healing Systems - Nisher Ahmed; Md Emran Hossain; S M Shadul Islam Rishad; Arafath Bin Mohiuddin; Md Imran Sarkar; Zakir Hossain (JURIHUM : Jurnal Inovasi dan Humaniora, 2024)
This work investigates and enhances innovative methods for autonomous cloud management with artificial intelligence, specifically self-healing and self-optimization. The study uses AI based anomaly detection, predictive maintenance and automated recovery to derive self-healing. To self-optimize, it employs machine learning algorithms to analyze existing workload patterns, anticipate resource utilization demand, and adjust resources dynamically. These techniques are tested and validated in a simulated cloud environment in terms of performance metrics like response time, throughput, and resource utilization.